Prescribing pattern of antipsychotic drugs during the years 1996–2010: a population‐based database study in Europe with a focus on torsadogenic drugs. (18th May 2016) - Oteri, Alessandro; Mazzaglia, Giampiero; Pecchioli, Serena; Molokhia, Mariam; Ulrichsen, Sinna Pilgaard; Pedersen, Lars; Poluzzi, Elisabetta; De Ponti, Fabrizio; Garbe, Edeltraut; Schink, Tania; Herings, Ron; Bezemer, Irene D.; et al.
Abstract : Introduction: Antipsychotic drugs (APDs) are used to treat several mental illnesses. Some APDs have long been known to be associated with QT prolongation, potentially leading to torsades de pointes (TdP) and sudden cardiac death (SCD). In 2005, thioridazine was withdrawn because of the risk of SCD, bringing further attention to the arrhythmogenic potential of APDs. Aim: The aim of the current study was to evaluate the use of APDs in five European countries during the years 1996–2010. Methods: A cohort study was conducted using prescription/dispensing data from seven healthcare databases [the AARHUS University Hospital Database (Denmark), the German Pharmacoepidemiological Research Database (GePaRD) (Germany), Health Search Database/Thales (HSD) and Emilia Romagna Regional Database (ERD) (Italy), PHARMO Database Network and Integrated Primary Care Information (IPCI) (the Netherlands) and The Health Improvement Network (THIN) (the UK), covering a population of 27 million individuals. The annual prescription rate of APDs was measured overall and for individual medications. APDs were classified as torsadogenic according to the Arizona‐CERT list. All analyses were stratified by age, gender and calendar year. Results: A total of 559 276 person‐years (PYs) of exposure to APDs was captured. The crude annual prescription rate of APD use ranged from 3.0/1000 PYs in ERD to 7.7/1000 PYs in AARHUS. Among APDs with established torsadogenic potential, thioridazine was the most frequently used medication in the UK. Haloperidol was commonly prescribed in Italy and the Netherlands. The use of APDs with torsadogenic potential was much higher in elderly patients. Conclusions: Substantial use of APDs with torsadogenic potential has been reported in Europe in recent years, in spite of increasing concerns about their arrhythmogenic potential. This use was even greater in elderly patients, who are at higher risk of SCD.